Dialogic Public Relations Practice Through Corporate Websites Of Manufacturing Corporations In China - Bai, Shuling (2017)
Corporate website has played an increasingly important role in China. Most Chinese corporate websites pay more attention to disseminating corporate information than building relationships with publics. Dialogic public relations is proved to be effective for relationship building on websites. This research aims to examine the dialogic public relations practice of Chinese manufacturing corporations through their websites. There are four research objectives: (1) to examine the characteristics of corporate websites in promoting communication and public relations; (2) to examine the characteristics of corporate websites in addressing various publics with tailored contents; (3) to examine the dialogic characteristics of corporate websites in facilitating dialogic relationship building; and (4) to provide strategies for corporate websites in promoting dialogic public relations.